Juridical Analysis Of Companies That Unilaterally Lay Off Employees And Severance Pay That Does Not Match The Length Of Service - Rhea Ditya Aulawi; Rahmayanti; Ismaidar (Yayasan Multidimensi Kreatif, 2024)
The problem of labor is a problem that we hear about in developing countries, including Indonesia. Related to this, termination of employment is one of them. As there is unilateral termination of employment carried out by companies in Indonesia. In this writing, the author uses normative legal research methods. Primary legal material is obtained from Law no. 13 of 2003 concerning labor and secondary legal material is obtained from a review of legal literature, especially labor, papers, internet and others. The implementation of termination of employment carried out by the company must be in accordance with Law No. 13 of 2003 concerning Manpower which states that termination of employment is carried out in several processes, namely holding deliberation between employees and the company, if it reaches a deadlock, the last resort is through the court to decide the case. For employees who have problems committing serious violations, they are immediately handed over to the police without asking permission from the authorities. And for employees who are about to retire can be submitted in accordance with the regulations. Similarly, employees who resign are regulated in accordance with company regulations and legislation. As a company's responsibility for laid-off workers where the law requires or requires the company to provide severance pay, award money, and rights replacement money. And regulations regarding severance pay, award money and reimbursement money are regulated in article 156, article 160 to article 169 of Law No. 13 of 2003 concerning Manpower.